2020
DOI: 10.3390/pharmacy8040217
|View full text |Cite
|
Sign up to set email alerts
|

Self-Instruction Video Versus Face-to-Face Instruction of Pharmacy Students’ Skills in Blood Pressure Measurement

Abstract: A modern approach to clinical skill education is the use of educational videos, yet there is a shortage of literature investigating the effect of self-instruction videos (SIVs) in pharmacy students. Therefore, our objective was to investigate whether an SIV is non-inferior compared to face-to-face instruction (FTFI) in acquiring blood pressure measurement skills. The participants in this randomized controlled study were pharmacy students. The control group was taught by FTFI, while the intervention group watch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…However, it might be more favorable if interactive features, for example, “click-forward pauses”, 46 “clickable bookmarks” or “hyperlinked index” 12 were used to navigate between segments. Moreover, a portion of students who watched the video in the scope of the abovementioned study suggested adding a voiceover to the descriptive slides 25 which was also mentioned by some students of the present evaluation. Therefore, adding voiceover might enhance such videos further.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…However, it might be more favorable if interactive features, for example, “click-forward pauses”, 46 “clickable bookmarks” or “hyperlinked index” 12 were used to navigate between segments. Moreover, a portion of students who watched the video in the scope of the abovementioned study suggested adding a voiceover to the descriptive slides 25 which was also mentioned by some students of the present evaluation. Therefore, adding voiceover might enhance such videos further.…”
Section: Discussionmentioning
confidence: 80%
“…This complies with our study prior. 25 However, the acceptance and also efficacy of educational videos might depend on the setting (for example teaching topic, incorporation of video with other teaching activities) in which the video is applied. For example, Bazyk et al compared videotaped demonstration to live demonstration in teaching a developmental evaluation to occupational therapy students and revealed that in their case students preferred live over videotaped instruction although both groups evaluated their learning experience as good.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations